Synchronous extraskeletal Ewing’s sarcoma/PNET and gallbladder carcinoma: a case report and literature review - Andrzej Plis; Aneta Zygulska; Mirosława Püsküllüoğlu; Wojciech Szczepański; Magdalena Białas; Maciej Krupiński; Krzysztof Krzemieniecki (Contemporary Oncology, 2017)
Ewing’s sarcoma (ES) and primitive neuroectodermal tumour (PNET) are now considered to be the same tumour and usually occur in long bones. Extraskeletal Ewing’s sarcoma is an extremely rare neoplasm, accounting for 1% of soft tissue sarcomas, with most common location in the thorax. Gallbladder cancer (GBC) represents the most common type among the biliary tract cancers with a poor prognosis even among patients undergoing aggressive therapy. We present study of extraskeletal ES/PNET found in the hilus of the liver of an elderly, diagnosed one month prior with GBC woman. The patient underwent two cycles of chemotherapy SAIME/SAVAC for ES and thereafter was operated. During three-year follow-up no recurrence of ES/PNET has been reported. However, two years after chemotherapy the patient suffered a relapse of adenocarcinoma of the gallbladder and thus received palliative chemotherapy of gemcitabine and cisplatin. After 16 months of recurrence she died. To the best of our knowledge, this is the first case of ES/PNET located in the hilus of the liver and as a synchronous neoplasm.